(untitled) (Revista Tempo e Argumento, 2021)
Resenha da obra: KHALIDI, Rashid. The Hundred Year´s War on Palestine: A History of Settler Colonial Conquest and Resistance. London: Profile Books, 2020. Edição Kindle.